Phytochemical Screening Infusion of Turmeric (Curcuma domestica val) and Red Ginger (Zingiber Officinale var roscoe) Rhizomes - Deri Islami; Denia Pratiwi; Zulkifli Zulkifli; Dini Mardhiyani (JURNAL PROTEKSI KESEHATAN, 2022)
The COVID-19 pandemic has an impact on the health of the entire community as an effort to prevent contracting the Corona virus, it can be done by strengthening the immune system by consuming supplements or concoctions from ingredients such as herbs from turmeric and red ginger rhizomes.Turmeric rhizome (Curcuma domestica val) and red ginger rhizome (Zingiber officinale var roscoe) have many benefits, one of which is to increase the immune system (immunomodulator). This study aims to identify secondary metabolites contained in the infusion of turmeric rhizome and red ginger rhizome. The method used is a color test with specific reagents to determine the content of secondary metabolites qualitatively which includes, alkaloids, flavonoids, triterpenoids/steroids, saponins and tannins. The extraction method used is the infusion method, the results of phytochemical screening tests from turmeric rhizome infusion contain alkaloids, flavonoids, triterpenoids/steroids and tannins. While the phytochemical screening of red ginger rhizome infusion contains flavonoids, tannins, triterpenoids, and saponins.